Salvia miltiorrhiza Bunge root in the treatment of myocardial fibrosis: research progress and challenges - Li, Qianrong; Ren, Chunzhen; Jiang, Bing; Wang, Xuehan; Wang, Chunling; Zhi, Xiaodong; Li, Linchan; Guo, Xiaoying; Zhao, Xinke; Li, Yingdong (Frontiers in Pharmacology, 2025)
Myocardial fibrosis (MF) involves the activation and excessive proliferation of cardiac fibroblasts (CFs) in the extracellular matrix, leading to increased collagen expression that impairs cardiac function. Currently, there are no effective pharmacological treatments for MF. Traditional Chinese Medicine (TCM), particularly Salvia miltiorrhiza Bunge [Lamiaceae; Salviae miltiorrhizae radix et rhizoma], has gained attention for its potential in treating MF. Recent studies indicate significant therapeutic effects of its active metabolites, supporting its use in MF treatment and positioning it as a promising candidate for drug development. Aim of the review: This article reviews the research and mechanisms of S. miltiorrhiza’s effective metabolites and preparations in treating MF, providing a reference for future clinical treatments. A systematic literature search was conducted in PubMed, Web of Science, CNKI, and Google Scholar (January 2000–October 2024) using keywords: “myocardial fibrosis,” “cardiac fibrosis,” “Salvia miltiorrhiza Bunge,” “extract,” and “botanical drug.” Results: The active metabolites of S. miltiorrhiza and its metabolite preparations exert anti-fibrotic effects through pleiotropic mechanisms, including suppression of ventricular remodeling, modulation of autophagy, inhibition of oxidative stress and cardiomyocyte apoptosis, and regulation of extracellular matrix homeostasis and immune-inflammatory responses. Conclusion: Research indicates that S. miltiorrhiza is beneficial for managing MF, but further studies are needed to identify its chemical metabolites and regulatory mechanisms. Large-scale, multi-center clinical trials are also necessary to assess treatment safety. This review offers insights for developing new anti-MF pharmacotherapies.